SuperCLASS – I. The super cluster assisted shear survey: Project overview and data release 1. Issue 2 (2nd April 2020) - Battye, Richard A; Brown, Michael L; Casey, Caitlin M; Harrison, Ian; Jackson, Neal J; Smail, Ian; Watson, Robert A; Hales, Christopher A; Manning, Sinclaire M; Hung, Chao-Ling; Riseley, Christopher J; Abdalla, Filipe B; et al.
ABSTRACT: The SuperCLuster Assisted Shear Survey (SuperCLASS) is a legacy programme using the e -MERLIN interferometric array. The aim is to observe the sky at L -band (1.4 GHz) to a r.m.s. of $7\, μ {\rm Jy}\, $ beam −1 over an area of $\sim 1\, {\rm deg}^2$ centred on the Abell 981 supercluster. The main scientific objectives of the project are: (i) to detect the effects of weak lensing in the radio in preparation for similar measurements with the Square Kilometre Array (SKA); (ii) an extinction free census of star formation and AGN activity out to z ∼ 1. In this paper we give an overview of the project including the science goals and multiwavelength coverage before presenting the first data release. We have analysed around 400 h of e -MERLIN data allowing us to create a Data Release 1 (DR1) mosaic of $\sim 0.26\, {\rm deg}^2$ to the full depth. These observations have been supplemented with complementary radio observations from the Karl G. Jansky Very Large Array (VLA) and optical/near infrared observations taken with the Subaru, Canada-France-Hawaii, and Spitzer Telescopes. The main data product is a catalogue of 887 sources detected by the VLA, of which 395 are detected by e -MERLIN and 197 of these are resolved. We have investigated the size, flux, and spectral index properties of these sources finding them compatible with previous studies. Preliminary photometric redshifts, and an assessment of galaxy shapes measured in the radio data, combined with a radio-optical cross-correlation technique probing cosmic shear in a supercluster environment, are presented in companion papers.